white regulates proliferative homeostasis of intestinal stem cells during ageing in Drosophila. - Sasaki, A.; Nishimura, T.; Takano, T.; Naito, S.; Yoo, S.K. (Nature metabolism, 2021)
Tissue integrity is contingent on maintaining stem cells. Intestinal stem cells (ISCs) over-proliferate during ageing, leading to tissue dysplasia in Drosophila melanogaster. Here we describe a role for white, encoding the evolutionarily conserved ATP-binding cassette transporter subfamily G, with a particularly well-characterized role in eye colour pigmentation, in ageing-induced ISC proliferation in the midgut. ISCs increase expression of white during ageing. ISC-specific inhibition of white suppresses ageing-induced ISC dysregulation and prolongs lifespan. Of the proteins that form heterodimers with White, Brown mediates ISC dysregulation during ageing. Metabolomics analyses reveal previously unappreciated, profound metabolic impacts of white inhibition on organismal metabolism. Among the metabolites affected by White, tetrahydrofolate is transported by White, is accumulated in ISCs during ageing and is indispensable for ageing-induced ISC over-proliferation. Since Thomas Morgan's isolation of a white mutant as the first Drosophila mutant, white mutants have been used extensively as genetic systems and often as controls. Our findings provide insights into metabolic regulation of stem cells mediated by the classic gene white.